Penggunaan Metode Multi-criteria Decision Aid dalam Proses Pemilihan Supplier - Indra Cahyadi (Performa: Media Ilmiah Teknik Industri, 2004)
Nowdays, an increasing trend in industrial companies is to conduct outsourcing for those products and activities considered to be outside the company's core business. Because of the financial importance and the multi-objective nature of supplier selection decision, in this paper we make an effort to highlight those crucial aspects to process qualitative and quantitative performance measures. In this paper, we use a multi-criteria decision aid method (PROMETHEE) to solve such problems, and then perform a sensitivity analysis to analyze simultaneous change of the weights importance of performance criteria. The whole suppliers selection model presented here (PROMETHEE techniques plus sensitivity analysis) seems to be a useful tool inside the final decision phase of a supplier selection process.